2021
DOI: 10.3390/cells10102606
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the EPHA2 Tyrosine-Kinase Domain Dysregulates Cell Pattern Formation and Cytoskeletal Gene Expression in the Lens

Abstract: Genetic variations in ephrin type-A receptor 2 (EPHA2) have been associated with inherited and age-related forms of cataract in humans. Here, we have characterized the eye lens phenotype and transcript profile of germline Epha2 knock-in mutant mice homozygous for either a missense variant associated with age-related cataract in humans (Epha2-Q722) or a novel insertion-deletion mutation (Epha2-indel722) that were both located within the tyrosine-kinase domain of EPHA2. Confocal imaging of ex vivo lenses from Ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 72 publications
(110 reference statements)
0
21
0
Order By: Relevance
“…EphA2 signals through the Src and cortactin pathway to influence actin cytoskeleton in equatorial lens epithelial cells to regulate hexagon cell shape and cell organization ( Cheng et al, 2013 ), similar to interactions previously shown in other tissues between EphA2 and Src ( Baldwin et al, 2006 ; Parri et al, 2007 ; Faoro et al, 2010 ). A recent study has confirmed complex formation between EphA2 and Src kinase thereby supporting their direct downstream interaction ( Zhou et al, 2021 ). The development and maintenance of the lens’ unique structure are determined by growth factors and signaling pathways ( Beebe et al, 1987 ; Belecky-Adams et al, 1997 ; Faber et al, 2002 ; Lovicu and McAvoy, 2005 ).…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…EphA2 signals through the Src and cortactin pathway to influence actin cytoskeleton in equatorial lens epithelial cells to regulate hexagon cell shape and cell organization ( Cheng et al, 2013 ), similar to interactions previously shown in other tissues between EphA2 and Src ( Baldwin et al, 2006 ; Parri et al, 2007 ; Faoro et al, 2010 ). A recent study has confirmed complex formation between EphA2 and Src kinase thereby supporting their direct downstream interaction ( Zhou et al, 2021 ). The development and maintenance of the lens’ unique structure are determined by growth factors and signaling pathways ( Beebe et al, 1987 ; Belecky-Adams et al, 1997 ; Faber et al, 2002 ; Lovicu and McAvoy, 2005 ).…”
Section: Introductionmentioning
confidence: 83%
“…Recently, disruption of Eph-ephrin signaling in human patients has been associated with congenital and age-related cataracts, defined as any opacity in the transparent eye lens ( Shiels et al, 2008 ; Jun et al, 2009 ; Zhang et al, 2009 ; Kaul et al, 2010 ; Tan et al, 2011 ; Sundaresan et al, 2012 ; Dave et al, 2013 ; Patel et al, 2017 ; Berry et al, 2018 ; Zhai et al, 2019 ). Mouse models are now being used to understand the mechanism of cataractogenesis ( Cooper et al, 2008 ; Jun et al, 2009 ; Cheng and Gong, 2011 ; Shi et al, 2012 ; Cheng et al, 2013 ; Son et al, 2013 ; Biswas et al, 2016 ; Cheng et al, 2017 ; Cheng et al, 2021 ; Zhou et al, 2021 ; Cheng et al, 2022 ). In this review, we highlight the different functions of Eph-ephrin signaling in the lens, describe how genetic background influences cataract phenotypes, as well as provide some insights into future directions and potential therapeutic strategies that can be tested to understand the pathogenesis of age-related cataracts.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations